The Influence Of Compensation And Work Motivation On Employee Performance At CV. Surya Mega Yosaka Mojokerto - Adiwati, Mei Retno; Ghifarian, Muhammad Sabil (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
HR plays an important role for an organization, to help and advance an organization, everything depends on existing human resources. Therefore, HR can determine the results of an organization in the long term. However, in reality there are many challenges that employees must face in supporting the successful performance of a company. The purpose of this research is to determine the effect of compensation and work motivation on employee performance. The method used is a quantitative method with a population of 77 samples taking the entire population of 77 production employees. Data was obtained through a questionnaire compiled based on indicators for each research variable and then analyzed using SmartPLS software. The results of the research show that compensation has no effect on employee performance and work motivation has a significant effect on employee performance.